Feasibility Study for Construction of N-Type HJT Solar Cell Manufacturing Plant with Production Capacity of 2 GWp in Batang Industrial Estate, Indonesia - Oetomo, Dedy Setyo; Adwiyah , Rabiatul (Journal of Social Science and Business Studies, 2025)
This study evaluates the technical and economic feasibility of establishing a 2 GWp N-Type heterojunction (HJT) solar cell manufacturing facility in Batang Industrial Estate, Indonesia. The proposed plant utilizes predominantly Chinese-manufactured equipment for key processes including PECVD systems, metallization lines, and testing equipment, with silicon wafers as the primary raw material. A comprehensive analysis incorporating technical, financial, operational, and market aspects demonstrates project viability with an IRR of 18.2% and payback period of 5.3 years. The total investment of USD 850 million encompasses equipment, infrastructure, and working capital. Results indicate favorable technical feasibility with established equipment manufacturers meeting international quality standards. Financial analysis shows strong potential returns, supported by growing regional solar panel demand and Batang's strategic advantages. Key risks identified include silicon wafer price volatility, technological obsolescence, and market competition, with structured mitigation strategies proposed.